How does reduction in pain lead to reduction in disability in patients with musculoskeletal pain? - Shaygan, Maryam (J Pain Res, 2019)
PURPOSE: Reduction in pain following multidisciplinary treatment is most often associated with a reduction in disability. To further elaborate the relationship between pain intensity and disability, the present study investigated three main questions: first, whether multidisciplinary treatment leads to a significant improvement in pain, disability and psychological variables (depression, pain acceptance and catastrophizing). Second, it was examined whether pain reduction may account for significant changes in the psychological variables (pre- to follow-up change scores). Finally, it was analyzed whether the psychological changes mediate the association between reduction in pain and in disability after controlling for age, sex and pain history. PATIENTS AND METHODS: Patients suffering from chronic musculoskeletal pain (n=279) attended a German inpatient multidisciplinary program lasting 15 consecutive days on average, with self-report data collected at pretreatment, posttreatment and three-month follow-up. RESULTS: Repeated measures ANOVAs showed a significant improvement in pain intensity, disability, pain acceptance, catastrophizing and depression at posttreatment and follow-up. Univariate regression analyses revealed that changes in pain intensity accounted for significant changes in depression, pain catastrophizing and pain acceptance (pre- to follow-up change scores). The results of Multiple Mediation Procedure showed that pain reduction did affect reduction in disability through improvement of depression, catastrophizing and acceptance. CONCLUSION: Our findings support a cognitive-behavioral model of pain that posits an important role for pain-related cognitive and emotional processes in long-term outcomes following multidisciplinary pain treatment, in particular for the modulation of disability due to pain. The results add evidence to the notion that pain-related cognitions are dynamic features varying over time dependent on the internal situation. PERSPECTIVE: The current findings are relevant to the management of patients with musculoskeletal pain. The results support the notion that, in contrast with the view of enduring personality traits, pain-related cognitions and emotions reflect a situational response that varies over time.